Analyzing the Effectiveness of Marketing Communication within the Faculty of Mining and Geology, VŠB-TU Ostrava and Verifying Hypotheses - Rolčíková, Markéta; Tomášková, Yveta; Straková, Alena (Journal of Research in Educational Sciences, 2026)
University managers face dynamic changes of environment which constraints them to innovate current approaches to managing the communication and to implement such a marketing approach into the management system that requires a high-quality communication mix created on the basis of marketing research. This article deals with results of the questionnaire survey performed in newly enrolled students of the Faculty of mining and geology, VŠB-TU Ostrava. The questionnaire survey was focused on reasons and motives which lead students to attend the faculty as well as on learning those elements of the communication mix which are privileged by students and which affect them within choosing the course, faculty and school. The article also contains defined and tested hypotheses which either confirm or disconfirm premises, defined by the authors. Results of the survey analyzed shall become the basis for suggesting the ideal communication mix which may be utilized by the school management in order to improve the marketing mix and to make it more effective.